Beyond the Impasse – Reflections on Dissociative Identity Disorder from a Freudian–Lacanian Perspective - Meganck, Reitske (Frontiers in Psychology, 2017)
Dissociative Identity Disorder (DID) is a widely contested diagnosis. The dominant posttraumatic model (PTM) considers early life trauma to be the direct cause of the creation of alter identities and assumes that working directly with alter identities should be at the core of the therapeutic work. The socio-cognitive model (SCM), on the other hand, questions the validity of the DID diagnosis and proposes an iatrogenic origin of the disorder claiming that reigning therapeutic and socio-cultural discourses create and reify the problem. The author argues that looking at the underlying psychical dynamics can provide a way out of the debate on the veracity of the diagnosis. A structural conception of hysteria is presented to understand clinical and empirical observations on the prevalence, appearance and treatment of DID. On a more fundamental level, the concept of identification and the fundamental division of human psychic functioning are proposed as crucial for understanding the development and treatment of DID.